Development of Android-Based Mobile Learning Media in Educational Sciences Courses - Putra, Hamda Kharisma (Cognitive Development Journal, 2023)
The aim of this research is to develop learning facilities through Android-based mobile learning media that are suitable for use in educational science courses. With mobile learning, users can access learning content anywhere and at any time, without having to visit a certain place at a certain time. So, users can access educational content without being bound by space and time. This research is a development research that goes through several stages. The first stage is a preliminary study, carried out to determine the results of a needs analysis based on learning objectives, mass, and learning strategies in order to produce products that suit student needs. The second stage is design, namely designing product prototypes according to the results of the needs analysis. The third stage is product development. In this stage, Android media products are started to be developed. The fourth stage is to carry out a product feasibility test using a scale of 4. From the results of material expert validation, a score of 29 was obtained for the 8 aspects of the material tested with an average score of 3.6, which is very suitable for use. Meanwhile, from the results of the media expert validation test, a total score of 42 was obtained for the assessment of 12 media aspects with an average of 3.5 or very decent. The field test is testing the product with student respondents. The results of this study are prototypes of Android-based mobile learning media products that are suitable for use in education science courses.